Design of key technologies for intranet dynamic gateway based on DPDK - Fucai CHEN; Weizhen HE; Guozhen CHENG; Shumin HUO; Dacheng ZHOU (Tongxin xuebao)
Aiming at the problems of high packet processing delay and high overhead caused by IP hopping,active defense gateway system with multi-layer network deployment structure was designed and implemented based on the data plane development kit (DPDK).Firstly,based on the DPDK fast forwarding framework,forwarding and processing performance of the system were optimized.Secondly,for the dynamic random mapping gateway with three different types of IP addresses,an efficient IP address allocation algorithm and an unpredictable IP address conversion algorithm were designed.The experimental results show that the designed system can effectively reduce the rate of information acquisition of sniffing attack,while greatly improving the processing delay caused by dynamic hopping.